X-ray flares from runaway pair production in active galactic nuclei - Kirk, J. G.; Mastichiadis, A. (1992)
ACTIVE galactic nuclei (AGNs) exhibit high luminosity with rapid variability, especially in X-ray emission, for which the luminosity can be greater than that of a normal galaxy, and the variability timescale implies an emitting region in some cases smaller than one light hour1. The hard X-ray spectrum of AGNs is nonthermal, probably arising from an electron-positron pair cascade, with some emission reflected off relatively cold matter2,3. Energy can be pumped into a cascade by any process that produces relativistic pairs, but because electrons and positrons are hard to accelerate efficiently, there has been interest in models in which protons are accelerated4,5, and create relativistic electrons on interaction with a local radiation field6-8. Here we show that a sufficient column density of protons can lead to runaway pair production: photons generated by the relativistic pairs are the targets for the protons to produce more pairs. This process can produce X-ray flares with the observed characteristics, and our model predicts the maximum ratio of luminosity to source size ('compactness') as well as their spectrum in the early phases. The same mechanism may also be able to create the knots of synchrotron-radiating pair plasma seen in sources such as 3C273.
Keywords: active galactic nuclei; Astrophysics; Electron-Positron Pairs; Luminosity; X Ray Sources; X Ray Spectra